PENGARUH PENGGUNAAN MOLASES SEBAGAI SUMBER ENERGI PAKAN PENGUAT DALAM RANSUM TERHADAP PERTUMBUHAN TERNAK KELINCI - Wuysang, Sumarni; Rahasia, C. A.; Umboh, J. F.; Tulung, Y. L. R. (Universitas Sam Ratulangi, 2017)
UTILIZATION EFFECT OF MOLASSES AS ENERGY SOURCE IN THE DIETS ON GROWING RABBIT PERFORMANCE. Molasses had been used previously in animal feeds. The present study was conducted to determine the effect of molasses utilization in the diets on growing rabbits. The study was conducted during five weeks at Department of Animal and Feed Science Laboratory, Faculty of Animal Husbandry, University of Sam Ratulangi, Manado. Twenty eight-weeks weaned female rabbits with an initial body weight of 600 -700 gr were used in this trial. Animals were allocated in an individual cage. A Completely Randomized Design (CRD) with 4 treatments and 5 replications was used for analysis of variance. Treatments were formulated as follow: R0 = 100% basal diet + 0% molasses; R1 = 98% basal diet + 2% molasses; R2 = 96% basal diet + 4% molasses; and R3 = 94% basal diet + 6% molasses. Variables measured were daily feed consumption, water consumption, daily gain, and feed conversion. Research results showed that average daily feed consumption in the present study ranged from 58.1 to 60.4 g; daily water consumption from 127.2 to 163.8 liters; daily gain from 20.1 to 20.9 g; and feed conversion ratio of about 3.57 to 3.80. Statistical analysis revealed that utilization of molasses replacing part of basal diets up to 6% gave no significant differences on daily feed consumption, water consumption, daily gain, and feed conversion ratio.Â It can be concluded that molasses as an energy source can be utilized up to 6% in growing rabbit diets without any negative effects. Keywords: Molasses, diets, growing rabbits performance